Nitric oxide sensor based on carbon fiber covered with nickel porphyrin layer deposited using optimized electropolymerization procedure - Hrbác, Jan; Gregor, Cenek; Machová, Markéta; Králová, Jana; Bystron, Tomás; Cíz, Milan; Lojek, Antonín (Bioelectrochemistry (Amsterdam, Netherlands), 2007)
Electropolymerization regime of meso-tetrakis(3-methoxy-4-hydroxyphenyl) porphyrin is optimized to yield films possessing both electrocatalytical and permselective properties towards nitric oxide oxidation. The sensor composed of electrochemically oxidized carbon fiber, covered solely with nickel porphyrin derivative layer electropolymerized using our method, is characterized by high selectivity towards nitrite (1:600), ascorbate (1:8000) and dopamine (>1:80), determined by constant potential amperometry at 830 mV (vs. Ag/AgCl). Selectivity for ascorbate and dopamine as well as detection limit for NO (1.5 nM at S/N=3) is 5-10 times better than parameters usually reported for Nafion coated porphyrinic sensors. Nafion coating can further enhance selectivity properties as well as aids to the stability of the sensors' responses.
Keywords: Electrodes; Silver Compounds; Electrochemistry; Sensitivity and Specificity; senzitivita a specificita; dopamin; Carbon Fiber; Catalysis; elektrochemie; Biosensing Techniques; Ascorbic Acid; Nitrites; oxidace-redukce; Fluorocarbon Polymers; elektrody; oxid dusnatý; fluorokarbonové polymery; biosenzitivní techniky; Nitric Oxide; Silver; dusitany; časové faktory; metaloporfyriny; Metalloporphyrins; kyselina askorbová; nikl; Carbon; stříbro; Nickel; Dopamine; sloučeniny stříbra; Oxidation-Reduction; uhlík; karbonové vlákno; Time Factors; katalýza